Nature of Free education in Nigeria: A Critical Reflection - Tella, Damilare G.; Agboga, Prosper Kofi; Segbefia, Samuel Kwabla (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
At different eras and regimes, the Nigerian national government have made several efforts to make education accessible to all through its free education policy. while some recorded remarkable success, others resulted into utter failure. The researcher felt the need to critically examine the concept of free education and probe into the very nature of the education itself. The researcher adopted the inductive approach by raising questions. The findings of this paper is that education cannot be entirely free, as there is always a price to pay and the nature of the education itself betrays its primary purpose and consequently, other purposes. Borrowing from existing examples, this paper suggested some tactical and strategic reforms and concluded that Nigeria’s education, which is “free” would not be its own until radical reforms are made.
Keywords: Cost; Constraint; Free education; Critical reflection